Culture and sensitivity analysis in rhinitis atrophic: case series - Tjahyadewi, Shelly; Aditomo, Rano; Rahayu, Rahayu; Sulistyanto, Agung; Pasaribu, Nurfauziati (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2024)
Atrophic rhinitis is a rare condition affecting the nasal mucosa, characterized by progressive nasal congestion, foul odor, and thick nasal secretions. It is classified into two types: primary (idiopathic), where the cause remains unknown, and secondary, which develops due to another underlying condition. Primary atrophic rhinitis, often called ozaena (from the Greek word for